The Spiral Groove Bearing as a Mechanism for Enhancing the Secondary Flow in a Centrifugal Rotary Blood Pump. Issue 10 (2nd May 2013) - Amaral, Felipe; Groß‐Hardt, Sascha; Timms, Daniel; Egger, Christina; Steinseifer, Ulrich; Schmitz‐Rode, Thomas
Abstract The rapid evolution of rotary blood pump (RBP) technology in the last few decades was shaped by devices with increased durability, frequently employing magnetic or hydrodynamic suspension techniques. However, the potential for low flow in small gaps between the rotor and pump casing is still a problem for hemocompatibility. In this study, a spiral groove hydrodynamic bearing (SGB) is applied with two distinct objectives: first, as a mechanism to enhance the washout in the secondary flow path of a centrifugal RBP, lowering the exposure to high shear stresses and avoiding thrombus formation; and second, as a way to allow smaller gaps without compromising the washout, enhancing the overall pump efficiency. Computational fluid dynamics was applied and verified via bench‐top experiments. An optimization of selected geometric parameters (groove angle, width and depth) focusing on the washout in the gap rather than generating suspension force was conducted. An optimized SGB geometry reduced the residence time of the cells in the gap from 31 to 27 ms, an improvement of 14% compared with the baseline geometry of 200 μm without grooves. When optimizing for pump performance, a 15% smaller gap yielded a slightly better rate of fluid exchange compared with the baseline, followed by a 22% reduction in the volumetric loss from the primary pathway. Finally, an improved washout can be achieved in a pulsatile environment due to the SGB ability to pump inwardly, even in the absence of a pressure head.